A 12-year National Study of Suicide by Jumping From Bridges in Norway. Issue 4 (2nd October 2017) - Sæheim, Aleksandra; Hestetun, Ingebjørg; Mork, Erlend; Nrugham, Latha; Mehlum, Lars
Abstract : Studies from several countries suggest that erecting fences on bridges more commonly used for suicide by jumping may be an effective way of reducing the risk of suicide by jumping from these bridges. Distribution of suicides by jumping off bridges has not yet been studied on a national level in any country. This study included all suicides by jumping from high places registered in the Norwegian Cause of Death Registry (COD) in the period 1999–2010 (n = 319). Combining data from the COD registry and information from police records, 71 cases of suicide by jumping off a bridge were identified involving 36 bridges. This form of suicide constituted approximately 1% of all suicides in Norway in the period 1999–2010. Almost half of these suicides were registered at only 6 bridges. Three Norwegian bridges were secured during the observation period of this study. Two bridges had barriers installed on the full length of the bridge with 11 suicides registered before barriers were installed, and none after. On the 1 bridge that was only partially secured, no change in numbers of suicides was observed after barriers were installed. One-third of jumps from bridges occurred over land. We found that although suicide by jumping off bridges was a relatively rare event, there is a potential for saving lives by installing physical barriers on bridges that are more commonly used for suicide by jumping.